Edukasi Terstuktur Sebagai Upaya Merubah Perilaku Pencarian Pengobatan Pasien Hipertensi - Ode Irman (Universitas Pahlawan Tuanku Tambusai, 2021)
Hypertension is a non-communicable disease that causes various problems, complications and every year have increased. Prevention of complications and severity can be done by changing the wrong health seeking behaviour. So far the education provided is only limited to health counselling that has not been scheduled and implemented properly, therefore community service aims to change the health seeking behaviour in hypertensive patients through structured education. This activity was held at Nelle Public Health Center of Sikka Regency 4 times for 60 minutes with the method of lectures, questions and answers, sharing and discussion. Implementation of activities still pay attention to the COVID-19 protocol. A total of 32 people with hypertension were involved in this activity. The output produced is a change in the health seeking behaviour when the symptoms of the disease are felt by going to a health facility. For health workers to be able to carry out structured education regularly